JrATHB-12 mediates JrMYB113 and JrMYB27 to control the anthocyanin levels in different types of red walnut - Haifeng Xu; Guifang Wang; Xinying Ji; Kun Xiang; Tao Wang; Meiyong Zhang; Guangning Shen; Rui Zhang; Junpei Zhang; Xin Chen (Journal of Integrative Agriculture, 2024)
Red walnut has broad market prospects because it is richer in anthocyanins than ordinary walnut. However, the mechanism driving anthocyanin biosynthesis in red walnut is still unknown. We studied two types of red walnut, called red walnut 1 (R1), with a red pericarp and seed coat, and red walnut 2 (R2), with a red seed coat only. R1 mostly contained cyanidin-3-O-galactoside, while R2 contained a various amounts of cyanidin-3-O-galactoside, cyanidin-3-O-arabinoside, and cyanidin-3-O-glucoside. The LDOX-2 (LOC109007163) and LDOX-3 (LOC109010746) genes, which encode leucoanthocyanidin dioxygenase/anthocyanidin synthase (LDOX/ANS), were preliminarily indicated as the crucial genes for anthocyanin biosynthesis in R1 and R2, respectively. The MYB differential genes analysis showed that MYB27 and MYB113 are specifically expressed in the red parts of R1 and R2, respectively, and they are regarded as candidate regulatory genes. Ectopic expression in Arabidopsis and transient injection in walnut showed that both MYB27 and MYB113 were located in the nucleus and promoted anthocyanin accumulation, while MYB27 promoted the expression of LDOX-2, and MYB113 promoted the expression of LDOX-3 and UAGT-3. Yeast one-hybrid and electrophoretic mobility shift assays showed that MYB27 could only bind to the LDOX-2 promoter, while MYB113 could bind to the promoters of both LDOX-3 and UAGT-3. In addition, we also identified an HD-Zip transcription factor, ATHB-12, which is specifically expressed in the pericarp. After silencing the expression of ATHB-12, the R2 pericarp turned red, and MYB113 expression increased. Further experiments showed that ATHB-12 could specifically interact with MYB113 and bind to its promoter. This suggests that MYB27 controls R1 coloration by regulating LDOX-2, while MYB113 controls R2 coloration by regulating LDOX-3 and UAGT-3, but ATHB-12 can specifically bind to and inhibit the MYB113 of the R2 pericarp so that it becomes unpigmented. This study reveals the anthocyanin biosynthetic mechanisms in two different types of red walnut and provides a scientific basis for the selection and breeding of red walnut varieties.